2018
DOI: 10.1101/mcs.a002394
|View full text |Cite
|
Sign up to set email alerts
|

Small-cell transformation of ALK-rearranged non-small-cell adenocarcinoma of the lung

Abstract: Anaplastic lymphoma kinase (ALK) gene rearrangements are present in ∼5% of non-small-cell lung cancers (NSCLCs). These rearrangements occur because of a chromosomal inversion within the short arm of Chromosome 2, which results in the formation of the echinoderm microtubule-associated protein-like 4 (EML4)–ALK fusion oncogene. Whereas NSCLC transformation to SCLC is a rare phenomenon described in epidermal growth factor receptor (EGFR) mutant cancers primarily after treatment with targeted therapy, it is exceed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 14 publications
(18 reference statements)
0
13
0
Order By: Relevance
“…To the best of our knowledge, this is the rst time that an incidence of transformation in the EGFR wild type NSCLCs was reported. The majority of previous studies focused on EGFR mutant patients, only several individual cases reported the SCLC transformation from EGFR wild-type NSCLC [3,[17][18][19]. In our cohort consisting of 591 EGFR wild type patients, 11 transformed cases were identi ed in 113 individuals with repeat biopsy (11/113, 9.73%).…”
Section: Discussionmentioning
confidence: 95%
“…To the best of our knowledge, this is the rst time that an incidence of transformation in the EGFR wild type NSCLCs was reported. The majority of previous studies focused on EGFR mutant patients, only several individual cases reported the SCLC transformation from EGFR wild-type NSCLC [3,[17][18][19]. In our cohort consisting of 591 EGFR wild type patients, 11 transformed cases were identi ed in 113 individuals with repeat biopsy (11/113, 9.73%).…”
Section: Discussionmentioning
confidence: 95%
“…Gene mutations retrieved from ClinVar. Gene name, accession number, mutation, clinical significance and literature references are reported, respectivelyGeneAccessionMutationClinical significanceRefEGFRNM_005228.4(EGFR)c.2573T>G (p.Leu858Arg)Pathogenic-drug response([61])ERBB2NM_001005862.2(ERBB2)c.2223_2234dupATACGTGATGGCPathogenic/Likely pathogenic([62])(p.Ala745_Gly746insTyrValMetAla)ALKNM_004304.4(ALK)c.3522C>A (p.Phe1174Leu)Pathogenic/Likely pathogenic([63])PTENNM_000314.6(PTEN)c.697C>T (p.Arg233Ter)Pathogenic([64])KRASNM_004985.4(KRAS)c.437C>T (p.Ala146Val)([65])BRAFNM_004333.5(BRAF)c.1794_1796dup (p.Thr599_Val600insThr)Pathogenic-drug response([66])PI3KNM_006218.3(PIK3CA)c.3140A>G (p.His1047Arg)Pathogenic/Likely pathogenic([67, 68])AKT1NM_005163.2(AKT1)c.49G>A (p.Glu17Lys)Pathogenic/Likely pathogenic([69, 70])MEK/MAP2K1NM_002755.3(MAP2K1)c.167A>C (p.Gln56Pro)Pathogenic([71, 72])EML4-ALK-p16chr2:29446394..42552694 inversionPathogenic([73])…”
Section: Methodsmentioning
confidence: 99%
“…Although strongly associated with smoking, SCLC may also transform from a non–small cell lung carcinoma (NSCLC) as a resistance mechanism after targeted tyrosine kinase inhibitor therapy for EGFR , ALK , or ROS1 -mutated NSCLC 8–11…”
Section: Small Cell Lung Carcinomamentioning
confidence: 99%